Antimicrobial Resistance Pattern of Clinical Isolates of Pseudomonas aeruginosa from Urinary Tract Infections in Wukari, Taraba state, Nigeria (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
Pseudomonas aeruginosa is a potent nosocomial pathogen of immunocompromised individuals, causing several infections while also resisting chemotherapy with conventional antimicrobial agents. Hence, this study was carried out to determine the antimicrobial resistance pattern of P. aeruginosa associated with urinary tract infections (UTIs) in Wukari, Taraba State. Thirty (30) voided midstream urine were collected from clinically diagnosed UTI patients attending Wukari general hospital and cultured aerobically on MacConkey agar and cysteine-lactose-electrolyte-deficient (CLED) agar. Bacterial isolates were identified by Gram staining and conventional biochemical tests. Antimicrobial sensitivity testing was done using the modified Kirby-Bauer method of the disc diffusion test. A total of 46 uropathogens were isolated of which 8 (17.39%) were identified as P. aeruginosa. Of these 8 isolates, 6 (75%) were isolated from male patients while 2 (25%) were isolated from female patients. All isolates of P. aeruginosa were susceptible to imipenem, ofloxacin, gentamicin, and levofloxacin. The resistances included resistance to amoxicillin-clavulanate (100%), cefepime (87.5%), cefotaxime (87.5%), ampiclox (75%), ceftriaxone (62.5%), cefuroxime (62.5%), and nalidixic acid (37.5%). High resistance rates against penicillins and cephalosporins are an indication of intrinsic resistance in P. aeruginosa. Hence, chemotherapy with imipenem, ofloxacin, gentamicin, and levofloxacin should be regularly monitored to prevent the development of resistant strains.
Keywords: Pseudomonas aeruginosa; Uropathogens; Urinary tract infections; Antimicrobial resistance; Wukari